APLIKASI KOMPOS DAN Azotobacter sp. TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annuum L.) - Toago, Saddam P.; Lapanjang, Iskandar M.; Barus, Henry N. (AGROTEKBIS, 2017)
The aims of this research are to determine growth and production of chili (Capsicum annuum L.) provided compost and bacteria Azotobacter sp. This study used a randomized block design factorial with two treatment factors. The first factor is compost consisting of : compost 15 t ha-1, 20 tha-1, and 25 t ha-1. The second factor is the bacteria Azotobacter sp. consisting of without giving Azotobacter sp. and giving Azotobacter sp. Each treatment was repeated four times so that there are 24 units trial. The results showed the bacteria Azotobacter sp. administration significantly affected plant height, root length, root volume, fresh weight of plants, plant dry weight, number of fruit crops, and the weight of the fruit crop. The results showed plant height, root length, root volume, fresh weight of plants, plant dry weight, number of fruit crops, and the weight of the fruit crop the highest in the delivery of Azotobacter sp. is each by 42,1 cm, 238,4 cm, 8,88 ml, 22,1 g, 5,60 g, 4,92 buah, 5,79 g. While the treatment of compost and their interaction had no significant effect on the observed variables.Â Key Words : Azotobacter sp., Chili, Compost, growth, production.Â